In silico test of brotowali (Tinospora crispa) as potential anticancer agent targeting mTOR on colorectal cancer - Hanik Isnaini; Adinda Amalia Agustin RJ; Washeilatus Sholehah; Nida Sudarlina; Safina Oktafia; Luluk Ayu Khodariyah; Siwi Putri Mumpuni (Menara Perkebunan)
Colorectal cancer is one of the deadliest diseases in the world. Treatment to overcome colorectal cancer has been pursued in such a way. Still, theresults are unsatisfactory, so treatment turns to herbal plants such as brotowali (Tinospora crispa) as an alternative colorectal anticancer. T.crispa is one of the herbal plants that contains a typical compound in the form of N-acetylnornuciferine and alkaloid-derived active compounds in the form ofN-formylanonaine, N- trans-coumaroyltyramine, and Tyramine which are potential as colorectal anticancer agents. The study used the mTOR(Mammalian Target of Rapamycin) receptor with PDB code (4DRJ) with its native ligand, RAP (receptor-associated protein). This study aims to analyze the potential of colorectal anticancer targeted by active compounds of alkaloid derivatives in T.crispa against mTOR. The method used is to explore active compounds through the KnapSack web and 3D protein structures on NCBI, docking validation using PyMol, tethering compounds N-acetylnornuciferine, N-formylanonaine, N-trans-coumaroyltyramine, and Tyramine to the target ligand using Pyrx and then visualized using BIOVIA Discovery Studio Visualizer. Analysis of the in silico test results showed that the compounds of N-acetylnornuciferine, N-trans-coumaroyltyramine, and Tyramine in T.crispa have good potential as colorectal anticancer agents in low doses but are not recommended for people with heart disease.